1985
DOI: 10.1007/bf02554156
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous carcinoma of the colon

Abstract: Two cases of primary adenosquamous carcinomas of the sigmoid colon and rectum are presented. Clinical features and pathologic findings of both primary and metastatic lesions are reported (including immunohistochemistry and electron microscopy). We emphasize that the presence of a metastatic squamous tumor in a patient with an unknown primary does not exclude the possibility of colonic carcinoma. Comparison with other reports in the American medical literature indicates that these are very aggressive tumors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

1987
1987
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 10 publications
0
11
0
3
Order By: Relevance
“…As regards the basaloid variety of squamous cell carcinoma outside the anal canal, it may arise from cloaco- genic embryologic nests, squamous metaplastic epithelium, or totipotential basal cells [12]. In mixed adenosquamous variety, Cerezo and others suggested that all such lesions be carefully evaluated by means of immunoperoxidase stains and/or electron microscopy in order to identify squamous features [20,21]. Symptoms, investigations, and assessment of patients with the divergent histologic subtypes of squamous cancer of the colon and rectum, including basaloid tumors, are similar to those of colon adenocarcinoma, as is evident in our case [5,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the basaloid variety of squamous cell carcinoma outside the anal canal, it may arise from cloaco- genic embryologic nests, squamous metaplastic epithelium, or totipotential basal cells [12]. In mixed adenosquamous variety, Cerezo and others suggested that all such lesions be carefully evaluated by means of immunoperoxidase stains and/or electron microscopy in order to identify squamous features [20,21]. Symptoms, investigations, and assessment of patients with the divergent histologic subtypes of squamous cancer of the colon and rectum, including basaloid tumors, are similar to those of colon adenocarcinoma, as is evident in our case [5,22].…”
Section: Discussionmentioning
confidence: 99%
“…Neoplastic nests invaded the wall of the rectum localized, focally, in the close proximity of the rectum's serosal surface. Seven (7) out of twenty (20) regional lymph nodes and a mesenteric lymph node were found to be infiltrated by malignant cells. The postoperative recovery of the patient was uneventful and she was discharged on postoperative day 9.…”
Section: Case Reportmentioning
confidence: 99%
“…Existe uma certa tendência de aumento do componente escamoso nas metástases. 6 Em nosso caso, as metástases foram decorrentes da disseminação de adenocarcinoma para o fígado.…”
Section: 247unclassified
“…1,7 A suspeita deve surgir em adenocarcinoma com áreas de tumor muito pouco diferenciado devendo ser pesquisados com imunoperoxidase e/ou microscopia eletrônica para identificação do componente escamoso. 6 O prognóstico de tumores estádio I e II com linfonodo negativo (Dukes A e B) é semelhante ao adenocarcinoma. Porém, na doença nodal, o prognóstico é pior.…”
Section: 247unclassified
See 1 more Smart Citation